MORPHOSYNTACTIC STRATEGIES FOR EXPRESSING EVIDENTIALITY IN UZBEK AND ENGLISH: A CONTRASTIVE ANALYSIS - Malika Ergasheva (TADQIQOTLAR, 2026)
Abstract. This study presents a contrastive analysis of the morphosyntactic strategies employed for expressing evidentiality in Uzbek and English. Evidentiality– the linguistic encoding of information source and the speaker’s basis for a claim–is realized through fundamentally different mechanisms in these typologically distant languages. Uzbek, as an agglutinative Turkic language, possesses a grammaticalized evidential system marked by dedicated verbal suffixes that obligatorily distinguish direct evidence from hearsay and inference. English, as an analytic Indo-European language, lacks grammaticalized evidentiality but expresses equivalent semantic distinctions through a range of lexical and syntactic strategies including modal verbs, adverbials, complement clause constructions, and reported speech patterns. Drawing on a parallel corpus of 500 sentence pairs extracted from literary, journalistic, and academic texts, this study identifies and classifies the evidential strategies of both languages, maps their functional correspondences, and analyzes the translation challenges that arise from the structural asymmetry between a grammatical and a lexical evidential system. Results demonstrate that Uzbek employs four primary morphological evidential markers, while English distributes equivalent functions across at least twelve distinct lexicosyntactic constructions, creating systematic non- equivalence in translation. The findings contribute to contrastive Turkic–Germanic linguistics and carry practical implications for translation studies, second language pedagogy, and the typological understanding of evidentiality across language families.